Meneropong Lembaga Pendidikan Islam Di Indonesia dengan Kacamata Filsafat Pendidikan - Fawait Syaiful Rahman; Dewi Ilma (Lembaga Penelitian dan Pengabdian Masyarakat STI. Blambangan Banyuwangi, 2020)
Abstract The journey of Islamic educational institutions from time to time is getting better. Changes in the national education system continue to be made to produce an education system that is by the basic visionary of the state, namely the education system that can produce professional outputs physically and mentally, recognized by the general public both at home and abroad. Research method using qualitative with the type of literature research. The results of the study concluded that Islamic educational institutions in Indonesia are following the philosophy of education. The philosophy of education captures the vision and mission in which the direction of education is headed. Islamic educational institutions in Indonesia will never be separated from the disposition of Indonesian society and culture.